Needs Analysis of Interactive Infographic Learning Media Development on Ecosystem Balance Material for Elementary Schools - Tania, Ayu; Raharjo, Makmum; Susanti, Rahmi (Journal of Educational Sciences, 2025)
The development of interactive infographic learning media helps present learning material in a more visual and engaging way. The first step in this process is analyzing the needs of students and teachers. This study focused on six key aspects: pedagogical, technical, cognitive, aesthetic, socio-cultural, and evaluation aspects. The research took place during the odd semester at Khalifah Annizam Islamic Elementary School in Palembang, involving 16 fifth-grade students and three teachers. A descriptive quantitative method was used to understand the needs of learners, teachers, and learning media. Data was collected through questionnaires and analyzed using the Guttman scale. The results showed that the highest average percentage in the medium category was found in the pedagogical aspect (61%), technical aspect (55%), socio-cultural aspect (70.8%), and evaluation aspect (56%). Other aspects were in the high and low categories. These findings indicate the need to improve these aspects by developing interactive infographic learning media to support a more effective learning process.